Afetividade institucional e desempenho de equipe: um estudo de caso em um hospital público e de ensino - Araújo, Regina Lúcia Moura de (2009)
The present search aims to understand the institutional affectivity in two work groups in the a public school hospital in Ceará state. An influent aspect on the decision of the development of the research for the hospital area was the relevance and the grandiosity of the actions done by those organizations, whose organizational culture has as nature the assistance to health and the concern about the practice of teaching. Other determining factors are related to the decisory process of the mentioned organizations which is generally carried out in superior spheres and also related to infrastructures which are characterized by precarization or permanent lack of material resource, inclusive lack of personnel, what demands workers’ bigger endeavor, and it may cause a work overloading. The main theoretical references were the studies on the theories about affectivity, affectivity at work, organizational culture and theories related to changes in contemporary work. In the research on institutional affectivity it was used the qualitative approach and had exploratory studies with bibliographical basis as a form of preparation and validity of a reference model of the Institutional Affectivity developed by the author. To the data analysis, establishing the relations between the two investigated groups, we used part of the referential of the suggested model. The results indicate that the Institutional Affectivity is related to team performance and organizational culture and is associated with the following factors: attitudes, confidence of the leader and collective action.